BIMBINGAN DAN KONSELING BERPERILAKU NAKAL PESERTA DIDIK - Sari, Eka Novita (LPPM STKIP PGRI Bandar Lampung, 2019)
This study aims to reveal the perceptions of elementary school teachers regarding student delinquency. This study used a qualitative approach, with a phenomenological case study design. The data analysis used was phenomenological analysis. The results of research on perceptions of elementary school teachers of